SAT0636-HPR PATIENT EXPERIENCE WITH THE PRESCRIPTION, INFORMATION AND USE OF METHOTREXATE. (13th June 2020) - Oton, T.; Carmona, L.; Andréu Sánchez, J. L.
Abstract : Background: Methotrexate (MTX) is currently a mainstream drug in the treatment of rheumatic diseases. However, the response to MTX is not universal and may be conditioned by a number of factors, among which adherence could be crucial. Objectives: The aim of this study is to explore adherence to MTX in patients with rheumatic diseases, facilitators and perceived when taking and maintaining the prescription. Methods: A qualitative study of content analysis was performed. Focus groups with patients taking either oral or subcutaneous MTX (being the main or coadjuvant treatment) for any rheumatic disease was performed. The groups were moderated by a rheumatologist that was unknown for the patients. The speech was recorded and transcribed. Subsequently, an inductive coding was performed with the help of Atlas.ti and main themes and sub-themes were extracted, with examples of verbatim anonymized speech. Results: Three focus groups were conducted, with a total of 12 participants, of whom eight were women, seven had rheumatoid arthritis, three had psoriatic arthritis, one had spondyloarthritis, and one had systemic lupus erythematosus. All patients reported an adequate adherence to treatment. The barriers identified were: information in the leaflet, technical language in the consults, difficult access to doctor´s appointment, social environment, side effects and the subcutaneous device. As facilitators, the following aspects were discussed: good predisposition of the physician, reliable graphic information, role of associations and partners support. The unmet needs detected were: problems with travelling, protocols for eventualities, absence of a plan of care, neglection of "non-physical" symptoms, disinformation on side effects and training in complementary aspects. Conclusion: Getting reliable information was the main barrier identified. The environment and side effects may also negatively impact on adherence. Shared decision making is a goal to be achieved in the future in these patients. Disclosure of Interests: Teresa Oton Consultant of: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution), Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution), José Luis Andréu Sánchez: None declared